Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
The Selected Issues paper examines policy challenges for inflation targeting in Hungary. It highlights that inflation targeting has been met with much initial success. A well-defined policy framework helped guide inflation expectations and provided an initial impetus toward resuming disinflation. The paper also focuses on the impact of aging on the public pension system. It describes the background underlying Hungary's current pension system, and provides a review of some of the recent work assessing Hungary's pension system viability.